(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
In this article key aspects on the poetic world of Chilean writer Delia Domínguez are discussed: transcended rurality, memoirs on German ancestors, natives and Spaniards, intercultural, feminist, peasant effects pertaining to Delia Domínguez´s poetry. Within this framework, historical and sociological references are analyzed. These references have to do with Chile´s southern farming setting where the poet was born, raised and lived up to her teenage years. All of this is crucial when analyzing Delia Domínguez´s poetics in accordance with the author of this article.